2018
DOI: 10.1002/adtp.201800051
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Triggered Delivery of Anticancer Therapeutics from MRI‐Visible Multilayer Microcapsules

Abstract: Although imaging‐guided drug delivery represents a noninvasive alternative to both surgical resection and systemic methods, it has seen limited clinical use due to the potential toxicity and fast clearance of currently available imaging agents. Herein, we introduce theranostic biocompatible microcapsules as efficient contrast‐enhanced imaging agents that combine magnetic resonance imaging (MRI) with ultrasound‐triggered drug release for real‐time tracking and targeted delivery in vivo. The 3‐μm diameter capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 95 publications
2
39
0
Order By: Relevance
“…Figure 9b shows MRI images of mice before and 2 h post-injection with BSA ultrasmall iron oxide nanoclusters, where the brain and kidney regions were significantly brightened, suggesting the nanoclusters remained in the blood stream even 2 h after injection. Similarly, ultrasmall iron oxide nanoparticles sandwiched between polymer layers of layer-by-layer assembled microcapsules showed not only increased blood circulation time, but also served as great drug nanocarriers for ultrasound-triggered drug release [27]. Figure 9c shows MRI images of a control mouse and a mouse 48 h post-injection, where the bright region near the heart suggested the long blood circulation time of these nanoparticle-loaded capsules.…”
Section: Biomedical Applications Of Iron Oxide Nanoclustersmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 9b shows MRI images of mice before and 2 h post-injection with BSA ultrasmall iron oxide nanoclusters, where the brain and kidney regions were significantly brightened, suggesting the nanoclusters remained in the blood stream even 2 h after injection. Similarly, ultrasmall iron oxide nanoparticles sandwiched between polymer layers of layer-by-layer assembled microcapsules showed not only increased blood circulation time, but also served as great drug nanocarriers for ultrasound-triggered drug release [27]. Figure 9c shows MRI images of a control mouse and a mouse 48 h post-injection, where the bright region near the heart suggested the long blood circulation time of these nanoparticle-loaded capsules.…”
Section: Biomedical Applications Of Iron Oxide Nanoclustersmentioning
confidence: 98%
“…Figure 5 shows representative TEM images of iron oxide nanoclusters that were produced with different matrices, where the polymer shells can be clearly seen (Figure 5a), but the silica and protein encapsulation formed matrix-iron oxide composite materials (Figure 5b,c). The matrix-assisted method has several distinctive advantages: first, drug molecules can be simultaneously encapsulated into the nanoclusters during the aggregation process, creating magnetic resonance imaging (MRI)-visible drug delivery vehicles; second, biocompatibility and water solubility can be easily achieved based on the choices of the matrices; and finally, by tuning the nanocluster sizes, other functionality can be achieved, such as ultrasound response [27].…”
Section: Matrix Encapsulation Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach modification to fabricate ultrasound sensitive capsule for drug delivery was adopted by Alford, et al. with a slight modification . In this work, the authors suggested that the incorporation of two layers of Fe 2 O 3 nanoparticles could enhance not only the MR contrast imaging but also the released profile of encapsulated DOX upon the application of ultrasound treatment .…”
Section: Stimuli Triggered Drug Release Capsulesmentioning
confidence: 99%
“…with a slight modification . In this work, the authors suggested that the incorporation of two layers of Fe 2 O 3 nanoparticles could enhance not only the MR contrast imaging but also the released profile of encapsulated DOX upon the application of ultrasound treatment . Besides that, the high hydrophilicity of the outer layer poly(N‐vinylpyrrolidone) could hinder the adhesion of protein, resulting to longer circulation of capsules in the bloodstream.…”
Section: Stimuli Triggered Drug Release Capsulesmentioning
confidence: 99%